Depth-stratified soil sampling for assessing nematode communities - Arieira, Giovani de Oliveira; Santiago, Débora Cristina; Franchini, Júlio Cezar; Guimarães, Maria de Fátima (Semina: Ciências Agrárias, 2016)
This study assessed the importance of stratified soil sampling on the detection (and therefore the distribution) of nematode communities and the differentiation of ecosystems by collecting stratified soil samples at intervals of 10 cm and non-stratified samples from 0 to 30 cm in two soil management systems (no-tillage and conventional tillage) and in a native forest fragment. The nematode frequency and prominence values were obtained after extraction by successive screening operations, sugar floatation clarification and the identification of nematodes to the genus level. The nematode communities were compared two-by-two based on Sorensen's community coefficient (CC) and the percentage similarity (PS). Relative abundances of functional guilds were subjected to a principal component analysis (PCA) and classified in dendrograms. Thirty-two edaphic nematode genera were found, and the nematode communities sampled on a non-stratified basis in the soil profile exhibited a high level of similarity because they could not be accurately characterized. Genera with low abundances were not detected. In the stratified samples, we were able to classify and group the nematodes present at different depths, mainly from 0 to 10 cm. Stratified soil sampling allowed a more accurate characterization and greater differentiation of nematode communities, identifying taxa that occurred at lower abundance levels, irrespective of frequency.